Production of Î²-D-galactosidase from Kluyveromyces fragilis in batch cultures with cheese whey as substrate - Xiomara Montiel; Ingrid Carruyo; José Ferrer; Letty Marcano; Zulay Mármol; Gisela Páez (Revista Técnica de la Facultad de Ingeniería, 2010)
The capacity of kluyveromyces fragilis (K. marxianus) ATCC 8554 to induce the production of β-D-galactosidase during growth in deproteinized cheese whey at temperatures of 25ºC and 29ºC and at initial pH of 4.5 was studied. Enzyme activity was determined in cell-free extracts evaluating the hydrolysis of o-nitrophenyl- β-D-galactopiranoside (ONPG), as substitute for lactose. Extraction of the enzyme from fresh cells was achieved by autolysis using 2% toluene. The enzyme was released lo the medium by permeabilization and partial digestion of the cell wall, without breaking, as reveled through electron microscopy. The highest activity, 0.604 µmol ortonitrophenol /ml/5min was obtained at 29ºC initiating estationary phase. The results obtained, including the production of biomase, ulilization of substrate and cell yield indicated the possibility of developing a bioprocess with cheese whey for the production of β-D galactosidase utilizing this microorganism.